Frequency Scanning Multibeamforming Method Based on CFBG Photonic Microwave Oscillation. (21st March 2023) - Mu, Ning; Guo, Hongxia; Gao, Wanrong
Abstract : In this paper, a two-loop photoelectric oscillator based on chirped fiber Bragg grating (CFBG) is used to construct a swept source, which acts on the frequency scanning array antenna to realise multibeamforming. The simulation results of the designed beamforming system have shown that it can realise wide-range beam scanning and has ultralow phase noise.